Mathematical modeling of thermodynamic effects in well bore zone of gas formation under hydraulic fracturing conditions - Bomba, A. Ya.; Myslyuk, M. A.; Yaroshchak, S. V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2015)
With the use of ideas of quasiconformal mapping and procedure of gradual recording of medium and process characteristic the methodology of mathematical modeling of filtration and mass-exchanging processes in well bore zone, upon conditions of occurrence of gas formation hydraulic fractures has been suggested. The influence of thermodynamic effects, caused by gas throttling through microfractures has been taken into consideration, when filtration process is described by specially modified Darcy’s law with critical pressure gradient. Numerical algorithm to solve correspondent boundary tasks, build flow pattern, temperature field, filtration properties etc. has been developed.